A bipolar plate and its preparation method and its application in proton exchange membrane water electrolyzer or proton exchange membrane fuel cell
Through layered composite strip structure and coating treatment, the problems of poor corrosion resistance, conductivity and stamping performance of bipolar plate materials are solved, and low-cost and high-performance bipolar plates are realized, which are suitable for proton exchange membrane water electrolytic cells and fuel cells.
Patent Information
- Application Number
- CN202210922523.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-02
- Publication Date
- 2025-08-12
- Estimated Expiration
- 2042-08-02
Smart Images

Figure CN115149021B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a bipolar plate and a preparation method thereof, and applications thereof in a proton exchange membrane water electrolyzer or a proton exchange membrane fuel cell. Background Art
[0002] Hydrogen is a vital energy source, with renewable energy hydrogen production being a key development direction. Proton exchange membrane electrolyzer cells (PEMECs, or PEM electrolyzers for short) are well-suited to the volatility of wind and solar power generation and hold the greatest potential for green hydrogen production. However, PEM electrolyzers operate in demanding environments and place extremely high demands on their core materials and components, resulting in high costs and poor durability. Therefore, developing high-performance, low-cost, and long-life materials and components is essential for promoting the large-scale application of PEM electrolyzers.
[0003] PEMEC has a similar structure to proton exchange membrane fuel cells (PEMFCs), both consisting of a stacked assembly of core components, including bipolar plates (BPPs), diffusion layers (GDLs), and membrane electrodes (CCMs). The bipolar plate operating environment is characterized by strong acidity (pH 2-4), high potential (1.5-2V), and strong oxidation (O₂ production at the anode). Therefore, the bipolar plate material must possess excellent corrosion resistance, high conductivity, and a long lifespan. Currently, the substrates used for commercial metal bipolar plates are primarily stainless steel and titanium. Research has shown that stainless steel bipolar plates offer reasonable corrosion resistance, good stamping properties, and the ability to process complex flow fields. However, at potentials greater than 1.5V, the metal ions that dissolve from the corrosion of stainless steel can poison the membrane electrode, making it unsuitable for use in PEMEC oxygen-side bipolar plates. Titanium-based bipolar plates exhibit excellent corrosion resistance. At high overpotentials (1.5-2.0V), a passivation film forms on the surface, preventing metal ion dissolution and thus poisoning the membrane electrode. Therefore, titanium is currently the primary material used for PEMEC bipolar plates. However, titanium is a hexagonal metal with anisotropy, which results in poor stamping performance and is not conducive to fine flow field processing. In addition, the formed passivation film has poor conductivity, which increases contact resistance and reduces electrolysis efficiency. Existing technologies usually improve the corrosion resistance and conductivity of titanium by preparing a precious metal (Au, Pt, Ir, etc.) coating on the surface of the titanium material, but the precious metal coating will significantly increase the cost. Currently, there is an urgent need to develop a bipolar plate for PEM electrolyzers that is corrosion-resistant, highly conductive, easy to stamp, and low-cost. Summary of the Invention
[0004] In light of this, the present invention aims to provide a bipolar plate, a method for its preparation, and its application in a proton exchange membrane water electrolyzer or proton exchange membrane fuel cell. The bipolar plate provided by the present invention combines the advantages of corrosion resistance, high conductivity, easy stamping, and low cost, resulting in a low-cost, high-performance bipolar plate.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a bipolar plate, comprising a layered composite strip formed into a flow field structure and a coating disposed on the surface of the layered composite strip; from bottom to top, the layered composite strip comprises a substrate layer and a covering layer disposed on the surface of the substrate layer, the surface side of the covering layer being a flow field region, and the coating disposed on the surface of the covering layer;
[0007] The substrate layer includes at least one of an SS layer, an Al layer, a Cu layer, and a Ni layer, wherein the SS is stainless steel; the cladding layer includes at least one of a Ti layer, a Zr layer, a Ta layer, and a Nb layer; and the coating includes a transition metal nitride layer, a transition metal carbide layer, a transition metal nitride carbonide layer, or a carbon-based coating.
[0008] Preferably, from bottom to top, when the uppermost surface of the substrate layer in the layered composite strip is an SS layer or an Al layer, the lowermost surface of the cladding layer is not a Ti layer; when the lowermost surface of the cladding layer in the layered composite strip is a Ti layer, the uppermost surface of the substrate layer is not an SS layer or an Al layer.
[0009] Preferably, the specific composition of each layer of the layered composite strip is Nb / SS, Ta / SS, Nb / Al, Ti / Ta / SS, Ti / Ta / Al, Ti / Nb / SS or Ti / Cu / SS.
[0010] Preferably, the thickness of the layered composite strip is 0.08 to 3 mm; the thickness of the cladding layer is 5 to 50 μm, and the thickness ratio of the cladding layer to the substrate layer is 1:99 to 20:80.
[0011] Preferably, the transition metal nitride layer includes a TiN layer, a NbN layer, a ZrN layer, a TaN layer or a CrN layer; the transition metal carbide layer includes a TiC layer, a NbC layer, a ZrC layer, a TaC layer or a CrC layer; the transition metal nitride carbide layer includes a Ti(N,C) layer, a Nb(N,C) layer, a Zr(N,C) layer, a Ta(N,C) layer or a Cr(N,C) layer; the carbon-based coating includes a nano-amorphous carbon layer.
[0012] Preferably, the flow field structure is a "ridge-groove" structure, and the flow channel depth of the flow field structure is 0.3-1.5 mm and the width is 0.5-5 mm.
[0013] The present invention provides a method for preparing the bipolar plate described in the above technical solution, comprising the following steps:
[0014] Laminating the substrate layer and the cladding layer and rolling them to obtain a layered composite strip;
[0015] stamping the layered composite strip to form a layered composite strip having a flow field structure;
[0016] A coating is deposited on the surface of the covering layer of the composite strip with the flow field structure by using a plasma nitriding method or a plasma enhanced chemical vapor deposition method to obtain the bipolar plate.
[0017] Preferably, the rolling composite is cold rolling composite, warm rolling composite or hot rolling composite; the rolling composite is one-pass rolling or multiple-pass rolling, the reduction rate of the one-pass rolling is 48-83%, the single reduction rate of the multiple-pass rolling is 30-65%, and annealing heat treatment is performed after each rolling in the one-pass rolling or multiple-pass rolling, the annealing heat treatment temperature is 400-950°C, and the time of a single annealing treatment is 0.3-3h.
[0018] Preferably, during the stamping process, the stamping punch contacts the surface of the cladding layer in the layered composite strip, and the stamping die contacts the surface of the substrate layer in the layered composite strip.
[0019] The present invention provides the use of the bipolar plate described in the above technical solution or the bipolar plate prepared by the preparation method described in the above technical solution in a proton exchange membrane water electrolyzer or a proton exchange membrane fuel cell.
[0020] The present invention provides a bipolar plate comprising a layered composite strip formed into a flow field structure and a coating disposed on the surface of the layered composite strip. From bottom to top, the layered composite strip comprises a substrate layer and a cladding layer disposed on the surface of the substrate layer, the surface of the cladding layer being a flow field region, and the coating disposed on the surface of the cladding layer. The substrate layer comprises at least one of an SS layer, an Al layer, a Cu layer, and a Ni layer, wherein the SS is stainless steel. The cladding layer comprises at least one of a Ti layer, a Zr layer, a Ta layer, and a Nb layer. The coating comprises a transition metal nitride layer, a transition metal carbide layer, a transition metal nitride-carbon layer, or a carbon-based coating. The bipolar plate provided by the present invention has the following beneficial effects:
[0021] The present invention uses valve metal layers such as Ti layer, Zr layer, Ta layer, and Nb layer as covering layers, and uses cubic structure metal layers such as SS layer, Al layer, Cu layer, and Ni layer as substrate layers, wherein the covering layer can form a stable passivation film, solve the problem of corrosion and dissolution of the substrate layer, and improve the corrosion resistance of the substrate layer; the cubic structure metal in the substrate layer has strong plastic deformation ability and is easy to stamp and form, which can solve the problem of anisotropy or difficulty in deformation (such as Ta and Nb) of the covering layer (such as hexagonal metal Ti and Zr), and improve the stamping performance of the bipolar plate; therefore, the layered composite strip including the substrate layer and the covering layer can take into account the high durability of the covering layer metal and the high stamping processing performance of the substrate layer metal, and the low-cost substrate layer metal replaces part of the high-cost covering layer metal, and the usage of the covering layer metal is reduced, which can significantly reduce the cost of the bipolar plate compared to a single covering layer.
[0022] In addition, a coating is provided on the surface of the covering layer of the layered composite strip. The coating is a highly conductive and corrosion-resistant coating that can improve the corrosion resistance and conductivity of the bipolar plate. Moreover, after the coating fails, the underlying covering layer can continue to resist corrosion, ensuring durability and safety. In addition, compared with precious metal coatings, the cost of the coating is reduced by more than 50%.
[0023] Furthermore, the layered composite strip in the bipolar plate provided by the present invention is relatively thin, making it easy to punch precise flow channels, thereby increasing the volume power density of the proton exchange membrane water electrolyzer or proton exchange membrane fuel cell.
[0024] Therefore, the bipolar plate provided by the present invention has the advantages of corrosion resistance, high conductivity, easy stamping and low cost, and is a low-cost, high-performance bipolar plate.
[0025] The present invention provides a preparation method of the bipolar plate. The present invention stacks the substrate layer and the covering layer for rolling and compounding. The rolling and compounding method can tightly combine the metal of the covering layer and the metal of the substrate layer through metallurgical bonding, with strong interlayer bonding force, high surface quality, and dense covering material structure, which can avoid the gap problem caused by spraying or sputtering coating, and is very well adapted to subsequent stamping forming and surface coating. In addition, the rolling and compounding can adopt a roll-to-roll production process, which is conducive to low-cost mass production; the present invention adopts plasma nitriding or plasma enhanced chemical vapor deposition to deposit a coating on the surface of the covering layer of a composite strip with a flow field structure. The coating generated by the plasma nitriding or plasma enhanced chemical vapor deposition method has a dense structure and strong bonding force with the substrate, so that the coating has excellent corrosion resistance and conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the structure of the bipolar plate in the present invention;
[0027] Figure 2A top view of the flow field structure of the bipolar plate in the present invention;
[0028] Figure 3 for Figure 2 Cross-sectional view of the flow field structure of the bipolar plate. DETAILED DESCRIPTION
[0029] The present invention provides a bipolar plate, comprising a layered composite strip formed into a flow field structure and a coating disposed on the surface of the layered composite strip; from bottom to top, the layered composite strip comprises a substrate layer and a covering layer disposed on the surface of the substrate layer, the surface side of the covering layer being a flow field region, and the coating disposed on the surface of the covering layer;
[0030] The substrate layer includes at least one of an SS layer, an Al layer, a Cu layer, and a Ni layer, wherein the SS is stainless steel; the cladding layer includes at least one of a Ti layer, a Zr layer, a Ta layer, and a Nb layer; and the coating includes a transition metal nitride layer, a transition metal carbide layer, a transition metal nitride carbonide layer, or a carbon-based coating.
[0031] The structure of the bipolar plate provided by the present invention is as follows Figure 1 As shown below, combined Figure 1 Provide detailed explanation.
[0032] The bipolar plate provided by the present invention includes a layered composite strip formed into a flow field structure. From bottom to top, the layered composite strip includes a substrate layer and a cladding layer disposed on the surface of the substrate layer, with the surface side of the cladding layer forming a flow field region. In the present invention, the substrate layer includes at least one of an SS layer, an Al layer, a Cu layer, and a Ni layer. When the substrate layer includes two or more of the SS layer, Al layer, Cu layer, and Ni layer, it is a composite metal layer formed by two or more of the corresponding metal layers. In the present invention, the substrate layer is preferably one or two of the SS layer, Al layer, and Cu layer. The present invention has no particular requirements for the SS layer; stainless steel familiar to those skilled in the art can be used, specifically, 304 stainless steel or 316L stainless steel. In the present invention, the cladding layer includes at least one of a Ti layer, a Zr layer, a Ta layer, and a Nb layer. When the cladding layer includes two or more of the Ti layer, Zr layer, Ta layer, and Nb layer, it is a composite metal layer formed by two or more of the corresponding metal layers. In the present invention, the cladding layer is preferably one or two of the Ti layer, Ta layer, and Nb layer. In the present invention, from bottom to top, when the top surface of the substrate layer in the layered composite strip is a SS layer or an Al layer, the bottom surface of the cladding layer is preferably not a Ti layer; and when the bottom surface of the cladding layer in the layered composite strip is a Ti layer, the top surface of the substrate layer is preferably not a SS layer or an Al layer. This invention avoids direct contact between the SS layer or Al layer in the substrate layer and the Ti layer in the cladding layer. By using other metal layers in the substrate layer or other metal layers in the cladding layer as barrier layers or transition layers, it can prevent the formation of continuous intermetallic compounds between the SS layer or Al layer and the Ti layer, thereby facilitating stamping and preventing tearing at the seams of the layered composite strip. In the present invention, the specific composition of each layer of the layered composite strip is Nb / SS, Ta / SS, Nb / Al, Ti / Ta / SS, Ti / Ta / Al, Ti / Nb / SS or Ti / Cu / SS; taking Nb / SS as an example, SS indicates that the substrate layer is an SS layer, and Nb indicates that the cladding layer is a Nb layer; taking Ti / Ta / SS as an example, SS indicates that the substrate layer is an SS layer, Ti / Ta indicates that the cladding layer is a composite metal layer of a Ti layer and a Ta layer, and the Ta layer in the cladding layer is in contact with the SS layer in the substrate layer; taking Ti / Cu / SS as an example, Cu / SS indicates that the substrate layer is a composite metal layer of an SS layer and a Cu layer, Ti indicates that the cladding layer is a Ti layer, and the Ti layer is in contact with the Cu layer in the substrate layer.
[0033] In the present invention, the substrate layer is a cubic metal layer that is easy to stamp and form. This solves the anisotropic or difficult-to-deform issues of the cladding layer (e.g., hexagonal metals Ti and Zr) or the difficulty of deforming (e.g., Ta and Nb), thereby improving the stamping performance of the bipolar plate. The cladding layer is a valve metal layer that forms a stable passivation film, which solves the problem of corrosion and dissolution of the substrate layer and improves its corrosion resistance. Therefore, the layered composite strip can achieve both the high durability of the cladding layer metal and the high stamping performance of the substrate layer metal. Furthermore, the low-cost substrate layer metal replaces part of the high-cost cladding layer metal, which can reduce the cost of the bipolar plate.
[0034] In the present invention, the thickness of the layered composite strip is preferably 0.08 to 3 mm. When the thickness of the layered composite strip is less than 0.2 mm, the layered composite strip is also called a foil. When the bipolar plate provided by the present invention is used in a proton exchange membrane fuel cell (PEMFC), the thickness of the layered composite strip is further preferably 0.08 to 0.2 mm, and more preferably 0.1 to 0.2 mm. When the bipolar plate provided by the present invention is used in a proton exchange membrane water electrolyzer (PEMEC), the thickness of the layered composite strip is further preferably 0.2 to 2.5 mm, and more preferably 1 to 2 mm. The thin thickness of the layered composite strip in the bipolar plate provided by the present invention facilitates the stamping of precise flow channels, which can improve the volumetric power density of the proton exchange membrane water electrolyzer or proton exchange membrane fuel cell. In the present invention, the thickness of the cladding layer in the layered composite strip is preferably 5-50 μm, and the thickness ratio of the cladding layer to the substrate layer is preferably 1:99-20:80, specifically 1:99, 2:98, 5:95, or 20:80. When the cladding layer or substrate layer is a composite metal layer formed by two or more metal layers, the present invention has no particular requirements for the specific thickness of each metal layer in the cladding layer or substrate layer, as long as it meets the thickness requirements of the cladding layer and the substrate layer. In an embodiment of the present invention, when the layered composite strip has a total of two metal layer composite structures (such as Nb / SS, Ta / SS, or Nb / Al), the thickness of the cladding layer is further preferably 5-20 μm. When the layered composite strip has a total of three metal layer composite structures (such as Ti / Ta / SS, Ti / Ta / Al, Ti / Nb / SS, or Ti / Cu / SS), the thickness of the cladding layer is further preferably 10-50 μm. In the present invention, the cupping value of the layered composite strip is greater than that of a titanium material of the same thickness and less than or equal to that of a stainless steel material of the same thickness.
[0035] The bipolar plate provided by the present invention further includes a coating provided on the surface of the layered composite strip. Specifically, the coating is provided on the surface of the covering layer of the layered composite strip, and the coating includes a transition metal nitride layer, a transition metal carbide layer, a transition metal nitride carbonide layer or a carbon-based coating. When the bipolar plate provided by the present invention is used in a proton exchange membrane water electrolyzer (PEMEC), the coating is further preferably a transition metal nitride layer, a transition metal carbide layer or a transition metal nitride carbonide layer. In the present invention, the transition metal nitride layer preferably includes a TiN layer, a NbN layer, a ZrN layer, a TaN layer or a CrN layer; the transition metal carbide layer preferably includes a TiC layer, a NbC layer, a ZrC layer, a TaC layer or a CrC layer; the transition metal nitride carbonide layer preferably includes a Ti(N,C) layer, a Nb(N,C) layer, a Zr(N,C) layer, a Ta(N,C) layer or a Cr(N,C) layer; the carbon-based coating preferably includes a nano-amorphous carbon layer. In the present invention, the coating thickness is preferably 2 to 11 μm, more preferably 5 to 10 μm. The present invention provides a coating on the surface of the superstrate layer of the layered composite strip. The coating is a highly conductive, corrosion-resistant coating that improves the corrosion resistance and conductivity of the bipolar plate. Furthermore, after the coating fails, the underlying valve metal layer continues to resist corrosion, ensuring durability and safety. Furthermore, compared to precious metal coatings, the coating costs are reduced by more than 50%.
[0036] In the present invention, the flow field structure is preferably a "ridge-groove" structure, the flow channel depth of the flow field structure is preferably 0.3 to 1.5 mm, and the width is preferably 0.5 to 5 mm. Figure 2 and Figure 3 When the bipolar plate provided by the present invention is used in a proton exchange membrane fuel cell (PEMFC), the flow channel depth of the flow field structure is further preferably 0.3 to 1 mm, and the width is further preferably 0.8 to 1.2 mm. When the bipolar plate provided by the present invention is used in a proton exchange membrane water electrolyzer (PEMEC), the flow channel depth of the flow field structure is further preferably 0.3 to 1.2 mm, and the width is further preferably 1 to 5 mm.
[0037] The bipolar plate provided by the present invention has the advantages of corrosion resistance, high conductivity, easy stamping and low cost, and is a low-cost, high-performance bipolar plate.
[0038] The present invention provides a method for preparing the bipolar plate described in the above technical solution, comprising the following steps:
[0039] Laminating the substrate layer and the cladding layer and rolling them to obtain a layered composite strip;
[0040] stamping the layered composite strip to form a layered composite strip having a flow field structure;
[0041] A coating is deposited on the surface of the covering layer of the composite strip with the flow field structure by using a plasma nitriding method or a plasma enhanced chemical vapor deposition method to obtain the bipolar plate.
[0042] The present invention stacks the substrate layer and the cladding layer for rolling and compounding to obtain a layered composite strip. When the substrate layer or the cladding layer is a single metal layer, the substrate layer and the cladding layer can be made of corresponding commercially available materials; when the substrate layer or the cladding layer is a composite metal layer formed by several metal layers, the substrate layer or the cladding layer can be made of commercially available corresponding composite metal layer materials, or the metal layers of the substrate layer and the metal layers of the cladding layer can be stacked and directly rolled and compounded. In the present invention, the rolling compounding is preferably cold rolling compounding, warm rolling compounding or hot rolling compounding. In the present invention, the rolling compounding is preferably a single rolling or multiple rolling passes, and the multiple rolling passes are preferably 2 to 6 rolling passes; the reduction rate of the single rolling is preferably 48 to 83%, and the single reduction rate of the multiple rolling passes is preferably 30 to 65%, and each rolling pass in the single rolling or multiple rolling passes is preferably subjected to annealing heat treatment. In an embodiment of the present invention, a layered composite strip having a composition of Ti / Al, Ti / Cu / SS, Ti / Ta / SS, Ti / Ta / Al and Ti / Nb / SS is preferably prepared by cold rolling and one-pass rolling and compounding. In the present invention, the temperature of the annealing heat treatment is preferably 400-950°C, and the time of a single annealing heat treatment is preferably 0.3-3h, more preferably 1-2h; when the substrate layer includes an Al layer, the temperature of the annealing heat treatment is further preferably 400-500°C; when the substrate layer includes an SS layer, the temperature of the annealing heat treatment is further preferably 750-950°C; when the cladding layer includes a Ti layer, the temperature of the annealing heat treatment is further preferably 400-882°C. Through the annealing heat treatment, the present invention enhances the mutual diffusion bonding force of atoms at the atomic interface between the substrate layer and the cladding layer, reduces residual stress, eliminates continuous intermetallic compounds between the interfaces, and improves stamping forming performance. The present invention stacks the substrate layer and the covering material layer for roll bonding. The rolling bonding method can tightly bond the metal of the covering material layer and the metal of the substrate layer through metallurgical bonding, with strong interlayer bonding force, high surface quality, and dense covering material structure. It can avoid the gap problem caused by spraying or sputtering coating, and is very suitable for subsequent stamping and surface coating. In addition, the rolling bonding can adopt a roll-to-roll production process, which is conducive to low-cost mass production.
[0043] After obtaining the layered composite strip, the present invention performs stamping and forming on the layered composite strip to form a layered composite strip having a flow field structure. In the present invention, the flow field structure is the same as that in the above-described technical solution and will not be described in detail here. During the stamping and forming process, the punch contacts the surface of the cladding layer of the layered composite strip, and the die contacts the surface of the substrate layer of the layered composite strip. The flow field region to be stamped and formed is on one side of the cladding layer. The design margin of the flow channel depth of the stamping flow field is consistent with the material springback rate.
[0044] After obtaining the composite strip with a flow field structure, the present invention uses plasma nitriding or plasma-enhanced chemical vapor deposition to deposit a coating on the surface of the superstrate layer of the composite strip with a flow field structure to obtain the bipolar plate. The present invention uses plasma nitriding to deposit a transition metal nitride layer in situ on the surface of the superstrate layer. The process conditions of the plasma nitriding method preferably include: a bias voltage of 200 to 800 V, an H2:N2:Ar (volume ratio) of 1:1:(1 to 3), a deposition chamber pressure of 50 to 300 Pa, a deposition time of 1 to 4 hours, and a deposition temperature of 650 to 850°C. The present invention preferably adopts the plasma nitriding method to deposit a TiN layer on the surface of the covering layer whose outermost layer is a Ti layer; in an embodiment of the present invention, the plasma nitriding method is preferably used to deposit a TiN layer on the surface of the covering layer of a layered composite strip composed of Ti / Ta / SS, Ti / Ta / Al, and Ti / Nb / SS. The outermost layer of the covering layer is a Ti layer, which can generate a reaction layer of transition metal nitrides, and the second outermost covering layer (Nb or Ta) is a barrier layer. The diffusion coefficient of nitrogen in the barrier layer is lower than that of the reaction layer; during the plasma nitriding process, nitrogen atoms diffuse into the Ti layer, first forming a Ti(N) solid solution. After encountering the Nb or Ta barrier layer, the diffusion rate of the nitrogen atoms decreases. After the nitrogen atoms accumulate in the Ti layer, dense TiN is formed, eliminating the Ti(N) solid solution transition layer.
[0045] In the present invention, the process conditions of the plasma enhanced chemical vapor deposition method preferably include: a reaction temperature of 450 to 600°C, a radio frequency plasma power of 200 to 500W, and a working pressure of 10 to 200Pa; when depositing a transition metal nitride layer, a transition metal carbide layer, or a transition metal nitride carbide layer: introducing a precursor, wherein the precursor is preferably a halide of Ti, Nb, Zr, Ta, or Cr, specifically TiCl4, NbCl5, ZrCl4, TaCl5, TaF5, or CrF6; when Ar:N2: When H2 (volume ratio) = 1: (0.5~1): (0.5~1), the generated coating is a transition metal nitride layer; when Ar: N2: H2: CH4 (volume ratio) = 1: (0.5~1): (0.5~1): 1, the generated coating is a transition metal nitride carbonide layer; when Ar: H2: CH4 (volume ratio) = 1: (0.5~1): 1, the generated coating is a transition metal carbide layer; when depositing a carbon-based coating: no precursor is introduced, Ar: H2: CH4 (volume ratio) = 1: (0.5~1): 1.
[0046] The present invention adopts plasma nitriding or plasma enhanced chemical vapor deposition to deposit a coating on the surface of the covering material layer. The coating generated by plasma nitriding or plasma enhanced chemical vapor deposition has a dense structure and a strong bonding force with the substrate, so that the coating has excellent corrosion resistance and conductivity.
[0047] The present invention provides for the use of the bipolar plate described in the above technical solution or the bipolar plate prepared by the preparation method described in the above technical solution in a proton exchange membrane water electrolyzer or proton exchange membrane fuel cell. In this application, the superstrate layer side of the bipolar plate serves as the working surface of the bipolar plate flow field, resisting corrosion and hydrogen embrittlement in the working environment, while the substrate layer side of the bipolar plate serves as the back surface of the bipolar plate flow field.
[0048] The bipolar plate provided by the present invention, its preparation method, and its application in a proton exchange membrane water electrolyzer or a proton exchange membrane fuel cell are described in detail below with reference to the embodiments. However, these embodiments should not be construed as limiting the scope of protection of the present invention.
[0049] Example 1
[0050] A bipolar plate comprises a layered composite strip formed into a flow field structure (the layered composite strip comprises a substrate layer and a covering layer disposed on the surface of the substrate layer), and a coating disposed on the surface of the covering layer of the layered composite strip; wherein the covering layer is a valve metal Ta layer that easily forms a stable passivation film, the substrate layer is an SS layer with good stamping formability, the substrate layer and the covering layer form a Ta / SS layered composite foil having a thickness of 0.1 mm, and a Ta layer:SS layer (thickness ratio) of 5:95; the Ta / SS layered composite foil is stamped into a "ridge-groove" structure flow field with a flow channel depth of 0.4 mm and a width of 1 mm; and a TiN highly conductive and corrosion-resistant coating is deposited on the surface of the Ta layer.
[0051] The preparation method of the bipolar plate is as follows:
[0052] (1) Preparation of Ta / SS layered composite foil by cold rolling: After the surface of a Ta foil coil with a thickness of 0.1 mm and a 304 stainless steel thin strip coil with a thickness of 1.9 mm was degreased and decontaminated, the laminated material was sent to a coil-up reversible cold rolling mill and rolled in 5 passes with reductions of 63%, 40%, 40%, 40%, and 40%, respectively. Annealing treatment was performed after each rolling pass at a temperature of 800°C and a time of 1 h. After rolling and laminating, a Ta / SS layered composite foil with a thickness of 0.1 mm was formed. The Ta thickness in the foil was 5 μm and the thickness of the 304 stainless steel was 95 μm.
[0053] (2) The Ta / SS laminated foil was stamped into a flow field. The stamping reduction was 0.45 mm, and after rebound, the designed dimension remained at 0.4 mm, with a springback rate of 12.5%. During the stamping process, the punch of the stamping die contacted the Ta cladding layer, while the die contacted the SS substrate layer. Therefore, the flow field side was Ta, which has good corrosion resistance. After stamping, the interlayer bonding was good, and no cracks or peeling occurred.
[0054] (3) The TiN coating was prepared by plasma enhanced chemical vapor deposition. The precursor used was TiCl4, the reaction temperature was 480℃, the RF plasma power was 250W, Ar:N2:H2 (volume ratio) = 1:0.75:0.5, the working pressure was 75Pa, and the thickness of the generated titanium nitride coating was 7μm.
[0055] The bipolar plate provided in this embodiment can be used in a proton exchange membrane fuel cell (PEMFC).
[0056] The bipolar plate provided in this embodiment was tested in a stack. At an operating voltage of 2V, the current density was 2.3A / cm 2 After 100 hours of operation, the current density of PEMFC is 2.25A / cm 2 , showing good durability.
[0057] According to the "Proton Exchange Membrane Fuel Cell Part 6: Bipolar Plate Characteristics Test Method" (GB / T20042.6-2011) and the U.S. Department of Energy (DOE) test standard, the bipolar plate provided in this embodiment was subjected to an electrochemical corrosion test. The test results showed that in a corrosion environment of 0.5MH2SO4+2ppmF-, the corrosion current density was 0.45μA / cm 2 @0.6V; at a contact pressure of 1.5MPa, the contact resistance is 8.9mΩ·cm 2 The test performance of the bipolar plate can meet the requirements of proton exchange membrane fuel cells.
[0058] Compared with bipolar plates made of titanium, the cost of the bipolar plates made of Ta / SS layered composite foil in this embodiment is reduced by 55%.
[0059] Example 2
[0060] A bipolar plate comprises a layered composite strip formed into a flow field structure (the layered composite strip comprises a substrate layer and a cladding layer disposed on the surface of the substrate layer), and a coating disposed on the surface of the cladding layer of the layered composite strip. The cladding layer is a composite metal layer formed of a valve metal Ti layer and a Nb layer that are easily formed into a stable passivation film, and the substrate layer is an SS layer with good stamping performance. The substrate layer and the cladding layer form a Ti / Nb / SS layered composite strip having a thickness of 1 mm and a thickness ratio of Ti:Nb:SS of 1:1:98. The Ti / Nb / SS layered composite strip is stamped into a "ridge-groove" structure flow field with a flow channel depth of 1 mm and a width of 2 mm. A TiN highly conductive and corrosion-resistant coating is deposited on the surface of the Ti / Nb composite layer.
[0061] The preparation method of the bipolar plate is as follows:
[0062] (1) Preparation of Ti / Nb / SS layered composite foil by cold rolling: A 0.04 mm thick Ti / Nb composite foil (commercially available material, thickness ratio Ti:Nb = 1:1) coil and a 1.96 mm thick 316L stainless steel thin strip coil were subjected to surface degreasing and decontamination treatment, and then stacked and fed into a coil-up reversible cold rolling mill with a one-pass reduction rate of 50%. After rolling, the laminated foil was annealed at 850 °C for 2 h to form a 1 mm thick Ti / Nb / SS layered composite strip. The thicknesses of Ti, Nb, and SS in the strip were 10 μm, 10 μm, and 980 μm, respectively. Stainless steel contains many alloying elements and has a low solid solubility in titanium. When titanium is directly compounded with stainless steel, intermetallic compounds (IMC) such as σ phase, λ phase, TiC, Fe2Ti, FeTi, Cr2Ti and NiTi2 are often generated at the interface. These brittle IMC layers lead to very low interfacial bonding strength, which seriously affects its application in production. In this embodiment, a Ti / Nb composite layer is used as the cladding layer. The Nb in the cladding layer acts as a transition layer between the Ti in the cladding layer and the stainless steel in the substrate layer, which can solve the above problem. No continuous intermetallic compounds are generated between Nb, Ti and SS. Therefore, Nb and SS are in contact during rolling and compounding, and a metallurgical bond is formed after one rolling, thereby avoiding the generation of continuous intermetallic compounds.
[0063] (2) The Ti / Nb / SS layered composite strip is formed into a flow field by stamping. The front of the stamping die contacts the Ti / Nb cladding layer, while the concave die contacts the SS substrate layer. Therefore, the flow field side is the Ti / Nb with good corrosion resistance. After stamping, the interlayer bonding is good, and no cracks or peeling occur.
[0064] (3) In-situ generation of highly conductive and corrosion-resistant coatings by plasma nitriding: The Ti / Nb / SS layered composite strips were plasma nitrided at 750°C for 3 h, with a deposition chamber pressure of 200 Pa, a plasma nitriding bias of 600 V, and H2:N2:Ar (volume ratio) = 1:1:2. The activated nitrogen first penetrated into the outermost Ti metal layer to form a Ti(N) solid solution. As the nitriding time increased, the solid-dissolved nitrogen content gradually increased, and the depth of the nitrided layer gradually thickened. After penetrating the 10 μm Ti layer, it encountered the Nb layer. The diffusion rate of nitrogen in Nb was lower than that of Ti. As the nitriding time increased, the thickness of the nitrided layer no longer increased. After the nitrogen content in the Ti(N) solid solution increased, a dense TiN coating was generated, which improved corrosion resistance and conductivity.
[0065] The bipolar plate provided in this embodiment can be used in a proton exchange membrane water electrolyzer (PEMEC).
[0066] The bipolar plate provided in this embodiment was subjected to an electrochemical corrosion test according to the "Proton Exchange Membrane Fuel Cell Part 6: Bipolar Plate Characteristics Test Method" (GB / T 20042.6-2011) and the U.S. Department of Energy (DOE) test standard. The test results showed that under the conditions of an acidic environment with a pH value of 3 and a polarization potential of 2 V, the corrosion current density was 1.1 μA / cm 2 , under a contact pressure of 1.5MPa, the contact resistance is 14mΩ·cm 2 , meeting the requirements of PEMEC.
[0067] Compared with bipolar plates made of titanium, the cost of the bipolar plates made of Ti / Nb / SS layered composite strips in this embodiment is reduced by 60%.
[0068] It can be seen from the above embodiments that the bipolar plate provided by the present invention has the advantages of corrosion resistance, high conductivity, easy stamping and low cost, and is a low-cost, high-performance bipolar plate.
[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A bipolar plate, characterized in that: The invention is composed of a layered composite strip formed into a flow field structure and a coating provided on the surface of the layered composite strip; from bottom to top, the layered composite strip is composed of a base material layer and a covering material layer provided on the surface of the base material layer, the surface side of the covering material layer is a flow field area, and the coating is provided on the surface of the covering material layer; The substrate layer is at least one of an SS layer, an Al layer, a Cu layer, and a Ni layer, wherein the SS is stainless steel; the cladding layer is at least one of a Ti layer, a Zr layer, a Ta layer, and a Nb layer; and the coating is a transition metal nitride layer, a transition metal carbide layer, a transition metal nitride carbide layer, or a carbon-based coating; From bottom to top, when the uppermost surface of the substrate layer in the layered composite strip is an SS layer or an Al layer, the lowermost surface of the cladding layer is not a Ti layer; when the lowermost surface of the cladding layer in the layered composite strip is a Ti layer, the uppermost surface of the substrate layer is not an SS layer or an Al layer; The method for preparing the bipolar plate comprises the following steps: Laminating the substrate layer and the cladding layer and rolling them to obtain a layered composite strip; stamping the layered composite strip to form a layered composite strip having a flow field structure; Depositing a coating on the surface of the covering layer of the composite strip having the flow field structure by a plasma nitriding method or a plasma enhanced chemical vapor deposition method to obtain the bipolar plate; The rolling composite is cold rolling composite; the rolling composite is one-pass rolling or multiple-pass rolling, the reduction rate of the one-pass rolling is 48~83%, the single reduction rate of the multiple-pass rolling is 30~65%, and annealing heat treatment is performed after each rolling in the one-pass rolling or multiple-pass rolling, the annealing heat treatment temperature is 400~950℃, and the time of a single annealing treatment is 0.3~3h.
2. The bipolar plate according to claim 1, characterized in that The specific composition of each layer of the layered composite strip is Nb / SS, Ta / SS, Nb / Al, Ti / Ta / SS, Ti / Ta / Al, Ti / Nb / SS or Ti / Cu / SS.
3. The bipolar plate according to claim 1 or 2, characterized in that: The thickness of the layered composite strip is 0.08-3 mm; the thickness of the covering layer is 5-50 μm, and the thickness ratio of the covering layer to the substrate layer is 1:99-20:
80.
4. The bipolar plate according to claim 1, characterized in that The transition metal nitride layer includes a TiN layer, a NbN layer, a ZrN layer, a TaN layer or a CrN layer; the transition metal carbide layer includes a TiC layer, a NbC layer, a ZrC layer, a TaC layer or a CrC layer; the transition metal nitride carbide layer includes a Ti(N,C) layer, a Nb(N,C) layer, a Zr(N,C) layer, a Ta(N,C) layer or a Cr(N,C) layer; the carbon-based coating includes a nano-amorphous carbon layer.
5. The bipolar plate according to claim 1, characterized in that The flow field structure is a "ridge-groove" structure, and the flow channel depth of the flow field structure is 0.3~1.5mm and the width is 0.5~5mm.
6. The method for preparing a bipolar plate according to any one of claims 1 to 5, characterized in that: The following steps are involved: Laminating the substrate layer and the cladding layer and rolling them to obtain a layered composite strip; stamping the layered composite strip to form a layered composite strip having a flow field structure; Depositing a coating on the surface of the covering layer of the composite strip having the flow field structure by a plasma nitriding method or a plasma enhanced chemical vapor deposition method to obtain the bipolar plate; The rolling composite is cold rolling composite; the rolling composite is one-pass rolling or multiple-pass rolling, the reduction rate of the one-pass rolling is 48~83%, the single reduction rate of the multiple-pass rolling is 30~65%, and annealing heat treatment is performed after each rolling in the one-pass rolling or multiple-pass rolling, the annealing heat treatment temperature is 400~950℃, and the time of a single annealing treatment is 0.3~3h.
7. The preparation method according to claim 6, characterized in that During the stamping process, the stamping punch contacts the surface of the covering layer in the layered composite strip, and the stamping die contacts the surface of the base material layer in the layered composite strip.
8. Use of the bipolar plate according to any one of claims 1 to 5 or the bipolar plate prepared by the preparation method according to any one of claims 6 to 7 in a proton exchange membrane water electrolyzer or a proton exchange membrane fuel cell.
Citation Information
Patent Citations
Clad metal bipolar plates
US20070264540A1